Function-oriented synthesis of two-dimensional (2D) covalent organic frameworks - from 3D solids to 2D sheets - Li, Xing; Yadav, Priya; Loh, Kian Ping (Chemical Society reviews, 2020)
Covalent organic frameworks (COFs) are constructed from the precise integration of small organic blocks into an extended, porous framework via covalent linkages. COFs can also be viewed as an organic solid consisting of a periodic array of one dimensional (1-D) channels. Although a wide range of applications have been envisioned for COFs, understanding the structure-property correlation at the level of chemical linkages, topology, pore size and functionality is needed to unlock the potential of these materials. Herein, we review some emerging applications of two-dimensional (2D) COFs in solid-state photoluminescence, stimuli-responsive COFs, gas storage, ion conduction and energy storage, and discuss the intricate design principles that enable these COFs to perform better than their building blocks or polymeric counterparts. Going beyond bulk 2D-COFs, molecular thin organic layers called COFene can be derived from the exfoliation of 2D COFs, generating new properties for applications in optoelectronic devices, catalysis and separation. This review provides guidelines for the function-oriented synthesis of 2D COFs from 3D solids to 2D sheets.